Performance of Different Carnation (Dianthus Caryophyllus L.) Cultivars Grown from Seed in the Plains of West Bengal, India - Maitra, S.; Roychowdhury, N. (International Journal of Bio-resource and Stress Management, 2023)
The suitability of 6 spray carnation cultivars namely Chabaud Extra Mix, Enfont De Nice, Chabaud Mix, Chabaud Super Mix, Chabaud Finest Mix and Lilipot Mix grown from seeds were studied in the plains of West Bengal, India in this experiment. Plants of the variety Enfont De Nice was found longest (73.84 cm) and dwarfing nature was noticed with Lilipot Mix (47.38 cm). Highest numbers of side-shoots were recorded with Chabaud Extra Mix (18.12) and lowest with Enfont De Nice (12.80). Chabaud Mix produced highest number of leaves shoot-1 (21.38). Leaf length and leaf width were found highest with Enfont De Nice and lowest with Lilipot Mix. The plants of Lilipot Mix reached the Flower Bud Initiation (FBI) stage earliest (54.37 days) and the plants of Chabaud Extra Mix reached the FBI stage last of all (89.54 days). The shortest time period required for FBI to Colour Showing (CS) stage (34.75 days) was found with Chabaud Finest Mix. Cultivar chabaud Mix required the most delayed time period to reach the full bloom stage (5.08 days) and Chabaud Finest Mix reached the full bloom stage earliest (4.00 days). Longevity of flower in-situ was recorded maximum with Lilipot Mix (7.29 days). Bud length and bud diameter was found highest with Chabaud Super Mix (4.25 cm and 67 cm respectively). Flower diameter was found highest with Chabaud Super Mix (5.91 cm) and lowest flower diameter was recorded with Lilipot Mix (4.56 cm). Chabaud Extra Mix was found the highly floriferous variety producing 47.38 flowers plant-1. Longest stalks were produced by Chabaud Super Mix (35.43 cm). Higher fresh weight of 100 flowers was noticed with Enfont De Nice (254.88 g). Maximum post-harvest longevity was recorded with Lilipot Mix (4.63 days). Lilipot Mix is found to be better as pot plant for its short stalk length, earlier blooming with maximum in-situ longevity of flowers. The other cultivars are suitable for loose and cut flower production. Chabaud Super Mix can be used for quality flower production but the recommended most floriferous variety is Chabaud Extra Mix.